Uniform Estimates and Multisolvability of a Semilinear Elliptic Equation (Journal of Partial Differential Equations, 2007)
In this paper, the author gives the uniform estimates for the solutions of the semilinear elliptic equation Δu+λe^u = 0 with zero Dirichlet boundary condition, and then derive the uniqueness of the nonminimal solution assuming some conditions satisfied.
Keywords: Semilinear elliptic equation; uniform estimates; multisolvability